Часткове відображення моделей даних при інтеграції інформаційних систем - Константінов, С.М.; Пономаренко, Ю.Л.; Філатов, В.О. (Економіко-математичне моделювання соціально-економічних систем, 2016)
Methods for mapping for different structured database models are considered. Milestones to build a partial mapping are defined, including the mapping of database schemes and statuses.